Cooperative learning and group learning: The impact on high order thinking skills in the pythagorean theorem material - Suri, Fraulein Intan; Osella, Sonnia; Masykur, Ruhban; Widyastuti, Rany (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study aims to improve students High Order Thinking Skills through the application of the Group to Group Exchange learning model. The research method used is a quasi-experimental model with a Pretest-Posttest Control Group research design and a sampling technique using Cluster Random Sampling. The results showed that based on the research results obtained during the study, the average N-Gain Score for the experimental group using the Group to Group Exchange learning model was 59% with a minimum N-Gain Score of 51% and a maximum of 67%. While the average N-Gain Score control group with the Direct Instruction learning model is 39% with a minimum N-Gain Score of 34% and a maximum of 45%. This means that the Group to Group Exchange (GTGE) learning model is quite effective compared to the Direct Instruction (DI) learning model to improve students High Order Thinking Skill (HOTS).